Elevation of IgG antibodies against tissue transglutaminase as a diagnostic tool for coeliac disease in selective IgA deficiency - Korponay-Szabó, I R (Copyright 2003 by Gut, 2003)
Background: IgA serum autoantibodies against tissue transglutaminase (tTG) have an established diagnostic value in coeliac disease, and high efficacy tests are widely available for their detection. However, serological evaluation of IgA deficient subjects is still difficult. Aims: To evaluate the diagnostic potential of IgG class anti-tTG autoantibodies measured quantitatively using an enzyme linked immunosorbent assay (ELISA) compared with immunofluorescent detection of coeliac autoantibodies. Patients: We tested serum samples from 325 IgA deficient subjects, including 78 patients with coeliac disease, 73 disease controls, and 174 blood donors. Methods: IgG antibodies against human recombinant tTG were measured with an ELISA. IgG antiendomysium antibodies (EMA) were assayed by indirect immunofluorescence on human jejunum and appendix sections. Results: The IgG anti-tTG ELISA had a sensitivity of 98.7% and a specificity of 98.6%, and the correlation with IgG EMA titres was high (r(s)=0.91). One coeliac patient, initially negative in all autoantibody tests, displayed both IgG anti-tTG antibodies and IgG EMA during later gluten exposure. IgG anti-tTG antibodies and EMA titres showed significant decreases (p<0.001) in treated patients. The frequency of IgG anti-tTG autoantibody positivity was 9.8% among IgA deficient blood donors and 11 of the 12 positive subjects with known HLA-DQ haplotypes carried DQ2 or DQ8 alleles. Conclusions: IgG anti-tTG and IgG EMA autoantibody tests are highly efficient in detecting coeliac disease in IgA deficient patients. The high prevalence of coeliac antibodies among symptom free IgA deficient blood donors who also carry coeliac-type HLA-DQ genes indicates that all IgA deficient persons should be evaluated for coeliac disease.